Population-based prevalence of bronchiectasis and associated comorbidities in South Korea. Issue 2 (29th August 2019) - Choi, Hayoung; Yang, Bumhee; Nam, Hyewon; Kyoung, Dae-Sung; Sim, Yun Su; Park, Hye Yun; Lee, Jae Seung; Lee, Sei Won; Oh, Yeon-Mok; Ra, Seung Won; Kim, Sang-Heon; Sohn, Jang Won; et al.
Bronchiectasis is a chronic respiratory disease characterised by abnormal dilatation of bronchi, which presents clinically with cough, sputum production and recurrent infection [1]. Although bronchiectasis had been regarded as an "orphan" disease [2], recent studies have shown that the prevalence of bronchiectasis is increasing and this disease causes a significant burden on public health, including increased healthcare costs, hospital admission and mortality [3–5]. A nationally representative study reveals that bronchiectasis prevalence in the South Korean population might be higher than in Western populations http://bit.ly/2Z1ZZig